SPIO-loaded nanostructured lipid carriers as liver-targeted molecular T2-weighted MRI contrast agent - Zhu, Xiuliang; Deng, Xueying; Lu, Chenying; Chen, Ying; Jie, Liyong; Zhang, Qian; Li, Wei; Wang, Zuhua; Du, Yongzhong; Yu, Risheng (Quantitative Imaging in Medicine and Surgery; Vol 8, No 8 (September 30, 2018): Quantitative Imaging in Medicine and Surgery, 2018)
Background: Superparamagnetic iron oxide (SPIO) acts as a negative contrast agent in magnetic resonance imaging (MRI), and is widely used in clinical applications, including the diagnosis of hepatic diseases. Hepatocyte-targeted magnetic resonance contrast agents (MRCAs) can provide useful information for evaluating hepatic diseases. We prepared targeted magnetic nanostructured lipid carriers (MNLCs) to enhance the hepatocytes targeting efficiency. Methods: In vitro characterizations of MNLCs were determined by transmission electron microscopy (TEM). The cytotoxicity assay of the MNLCs was measured by methyl tetrazolium (MTT) method. The uptaken study was measured by confocal microscopy, flow cytometry and MRI in vitro. The enhanced liver-targeting efficiency of MNLCs was measured by fluorescence imaging and MRI in vivo. Results: Gal-NLC-SPIO was prepared successfully. The cytotoxicity assay of the MNLCs demonstrated that the MNLC had relatively low cytotoxicity and high biocompatibility for LO2 cells. More importantly, we confirmed that Gal-NLC-SPIO had greater uptake by LO2 cells than Gal-NLC-SPIO/PEG and free Gal in vitro. A liver distribution study of MNLCs in normal mice demonstrated that the fluorescent signal values to livers of the Gal-NLC-SPIO were significantly stronger than those of NLC-SPIO and Gal-NLC-SPIO/PEG. The liver targeting efficiency of Gal-NLC-SPIO was confirmed both in vitro and in vivo. Conclusions: We successfully developed liver-targeting MNLCs, which showed accurate hepatocytes targeting, and thus have the potential to be a new MRI contrast agent to help the diagnosis of liver diseases.